A longitudinal study of interest and membership in a fraternity, rape myth acceptance, and proclivity to perpetrate sexual assault. Issue 6 (18th August 2018) - Seabrook, Rita C.; McMahon, Sarah; O'Connor, Julia
ABSTRACT: Objective: This study explored the relation between interest and membership in a fraternity and acceptance of sexual violence (eg, rape myth acceptance, proclivity to perpetrate sexual aggression) among first year college men.Participants: A total of 315 men were surveyed before their first year of college (June–August 2010) and again at 4 time points over the next year.Methods: Participants responded to measures of rape myth acceptance and proclivity to perpetrate sexual aggression.Results: Interested members scored higher on proclivity to perpetrate sexual aggression and some rape myths than noninterested nonmembers; interested nonmembers scored in between the 2 groups.Conclusions: Results highlight the importance of considering both fraternity membership and interest in joining a fraternity, as well as examining individual rape myths, in studies of fraternity membership and sexual violence.